Circadian rhythmicity of heart rate variability and its impact on cardiac autonomic modulation in asthma. (2nd November 2021) - Sinha, Meenakshi; Behera, Ajoy K.; Sinha, Ramanjan; Parganiha, Arti; Pande, Babita; Sharma, Richa; Pati, Atanu K
ABSTRACT: The commonly observed nocturnal attack of asthma is accompanied by circadian variations in airway inflammation and other physiological variables. It is also documented to present with a significantly higher risk of adverse cardiovascular events that are associated with lower heart rate variability (HRV) and depressed sympathetic and enhanced parasympathetic modulations. However, available literature is scarce with regard to the impact of alteration in circadian rhythmicity of long-term HRV and its day–night variation in asthmatic patients. Thus, 72-h continuous recording of RR interval and oxygen saturation was done to study the circadian variability of HRV (in terms of time and frequency domain indices) and also to assess the pattern of alterations in sympathetic and parasympathetic tones at different times of the day in asthmatic patients ( n = 32) and healthy control subjects ( n = 31). Repeated-measure analysis of variance and independent-samples t -test revealed significantly increased parasympathetic tone [in terms of increased square root of the mean squared differences of successive NN intervals (RMSSD), percentage of number of pairs of adjacent RR interval differing by more than 50 ms (pNN50), standard deviation of NN intervals (SDNN), and high frequency (HF)] with reduced sympathetic activity [decreased low frequency (LF) and LF/HF ratio] at early morning hours (between 04:00 and 10:00 h) in the asthma patients in contrast to the healthy subjects who had opposite response. Also, significant phase delay (p<0.05) of all the HRV indices and SpO2, was evident by cosinor analysis. Therefore, disturbed circadian rhythm of HRV indices and early morning increased parasympathetic tone points toward the possible pathophysiological basis of exacerbated asthmatic symptoms at late night/early morning hours and susceptibility of future cardiovascular pathologies. This also necessitates the assessment of HRV rhythm while dealing with the therapeutic management of asthma patients.